2014
DOI: 10.1002/jor.22721
|View full text |Cite
|
Sign up to set email alerts
|

Temporal delimitation of the healing phases via monitoring of fracture callus stiffness in rats

Abstract: ABSTRACT:The healing process consists of at least three phases: inflammatory, repair, and remodeling phase. Because callus stiffness correlates with the healing phases, it is suitable for evaluating the fracture healing process. Our aim was to develop a method which allows determination of callus stiffness in vivo, the healing time and the duration of the repair phase. The right femurs of 16 Wistar rats were osteotomized and stabilized with either more rigid or more flexible external fixation. Fixator deformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…To our knowledge, this is the first study to attempt bone formation dynamics characterization during Masquelet’s second stage. Our results suggest that, similar to fracture healing, 1,6,9,16,42,55 new tissue formation occurs in a wave extending from the proximal and distal edges toward the defect center rather than extending from the membrane edges radially inward. Also like fracture healing, there is significant activity in 463 the first few weeks.…”
Section: Discussionmentioning
confidence: 59%
“…To our knowledge, this is the first study to attempt bone formation dynamics characterization during Masquelet’s second stage. Our results suggest that, similar to fracture healing, 1,6,9,16,42,55 new tissue formation occurs in a wave extending from the proximal and distal edges toward the defect center rather than extending from the membrane edges radially inward. Also like fracture healing, there is significant activity in 463 the first few weeks.…”
Section: Discussionmentioning
confidence: 59%
“…In another study, callus stiffness as monitored in vivo was found to determine maximum stiffness at 4 weeks with the stiff fixator, as compared to 9 weeks with the flexible fixator (Wehner et al. 2014). Thus, the stiff fixator can be considered to provide stable fixation and timely healing while the flexible fixator can be considered to be too flexible and to delay healing.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups use constrained torsion instead [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ], which is sensitive to embedding uncertainties, especially for shifting of the specimens’ axis of gravity creating a parallel offset to the fixed measurement axis of rotation. Furthermore, bending tests are established for ex vivo mechanical testing [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Bending tests have the potential to deliver robust values of the callus stiffness, independently of embedding errors, provided that the maximum callus expansion direction is consistently oriented relative to the loading direction for all investigated specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Non-destructive torsional testing is performed in rat [ 6 , 7 , 8 , 9 , 10 ] as well as in mouse experiments [ 11 , 12 , 13 , 14 ]. Bending is also performed in experiments for both species: three-point bending in rats [ 15 , 16 , 17 , 18 ] and mice [ 19 , 20 , 21 , 22 , 23 ] as well as four-point bending in rats [ 24 ] and mice [ 25 ].…”
Section: Introductionmentioning
confidence: 99%